Predictors of competitive advantage in information technology for SME entities: Knowledge management and innovation capabilities - Ahamat, Amiruddin; Ahmad Murad, Murzidah; Naser Alteneiji, Talal Mohammed Ahmed (Universal Publishers, 2024)
The purpose of this study is to identify the IT capabilities linked to innovation capabilities through knowledge management and analysing their impact on innovation capabilities.